Patterns and Business Scale of Milkfish Growing in East Tanete Riattang District, Bone Regency - Toto Hardianto; Mustafa Mustafa; Tamrin Tamrin; Feby Triadi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Pond cultivation is an effort to maintain and enlarge aquatic organisms in pond waters or ponds that are deliberately made by humans. This study aims to determine the pattern and scale of the milkfish enlargement business at the level of feasibility per unit of pond land. The research was conducted from January to July, 2020, in the Tanete Riattang Timur District, Bone Regency. Pond business patterns are grouped into three strata, namely monoculture milkfish (Chanos chanos fork), polyculture milkfish (Chanos chanos fork) and seaweed (Gracellaria verrucosa), polyculture milkfish (Chanos chanos fork) and shrimp with a narrow scale, medium and wide. Aquaculture business scale and pattern are analyzed by analyzing farmer income, R/C ratio analysis, Paybeack Period analysis, business feasibility analysis namely NVP analysis, IRR analysis and B/C Ratio analysis. The research results from a sample of Fisheries Households (RTP) Respondents. The highest financial feasibility of the milkfish (Chanos chanos fork). The financial feasibility of the milkfish (Chanos chanos fork) shrimp polyculture. The conclusion is that in general the ponds in Tanete Rianttang Timur District that are already operating are managed privately. The business feasibility category in East Tanete Riattang District is divided into two categories, namely very suitable and appropriate. From the NPV feasibility analysis, the IRR and BC ratio are included in the feasible category to be continued.